Bone health and multiple sclerosis. - Dobson, R; Ramagopalan, S; Giovannoni, G (2012)
People with multiple sclerosis (MS) have many reasons to have low bone mineral density and an increased fracture risk. Osteoporosis is a major cause of morbidity and mortality, and is more common in people with MS than the general population. A number of studies have examined the relationship between multiple sclerosis and reduced bone mineral density. In this topical review we seek to address the risk of low bone mineral density, osteoporosis and fractures associated with MS, and make practical suggestions as to how this pertinent issue may be approached in clinical practice.